The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1111/j.1432-1033.1988.tb14259.x
|View full text |Cite
|
Sign up to set email alerts
|

Monomerization of cytochrome oxidase may be essential for the removal of subunit III

Abstract: Incubation of cytochrome oxidase, under conditionsused as intial steps in treatment to remove sub‐unit III, causes at least partial monomerization of the enzyme. The extent of removal of subunit III by anion‐exchange fast protein liquid chromatography (FPLC) is much increased if the enzyme is fully monomerized before it is applied to the column. Subunit III is incompletely removed by chymotrypsin treatment. A digestion product of subunit III migrating in SDS‐PAGE like subunit IV, is detected with specific anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1989
1989
1995
1995

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…Despite the fact that COIII can be easily lost during purification, it is most probably a stoichiometric component of the oxidase complex in situ (Haltia et al, 1988;Bolgiano et al, 1988). Studies on the oligomeric state of the enzyme have suggested that CORI resides in the interphase between the monomers (Finel and Wikstrom, 1988 to be monomeric Finel, 1989). Studies on the oligomeric state of the enzyme have suggested that CORI resides in the interphase between the monomers (Finel and Wikstrom, 1988 to be monomeric Finel, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the fact that COIII can be easily lost during purification, it is most probably a stoichiometric component of the oxidase complex in situ (Haltia et al, 1988;Bolgiano et al, 1988). Studies on the oligomeric state of the enzyme have suggested that CORI resides in the interphase between the monomers (Finel and Wikstrom, 1988 to be monomeric Finel, 1989). Studies on the oligomeric state of the enzyme have suggested that CORI resides in the interphase between the monomers (Finel and Wikstrom, 1988 to be monomeric Finel, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Protein concentrations were measured according to Markwell et al (1978). SDS-PAGE, carried out using buffer system of Laemmli (1970) in 10-20% gradient acrylamide gels containing 5 M urea, and immunoblotting have been described by Finel and Wikstrom (1988). Paracoccus cytochrome aa3 was purified according to Bolgiano et al (1988) and Haltia et al (1988).…”
Section: Miscellaneousmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding of COIII to the other subunits appears to be sensitive to some detergents (e.g. dodecyldimethylamine N-oxide) and to alkaline pH (see Finel & Wikstrom, 1988). For instance, an incubation of the enzyme at pH 95 leads to the release of COIII.…”
Section: Subunit Himentioning
confidence: 99%
“…It has been postulated (Nalecz et al 1985;Finel & Wikstrom, 1988) that COIII The values are compiled from sedimentation equilibrium measurements. Minimal molecular weights are calculated from the amino acid sequences, assuming that the subunits are present in a 1:1 stoichiometry (Buse et al 1983;Kadenbach et al 1987).…”
Section: I I I I I I I I 1 I I I I I I I I I I I I I I I I I I I I mentioning
confidence: 99%